Is fire always the “bad guy”? - Fidelis, Alessandra [UNESP] (Elsevier, 2020)
Much distortion about the real role of fire in different ecosystems exists, mostly because fire events attract media attention, usually focusing on the negative aspects of fire. In the perception of the general public, fire events are usually linked to disasters that affect humans in several ways, from losses of lives to negative effects on human well-being. However, while some ecosystems are fire-sensitive and fire will thus bring more negative than positive effects (e.g. in tropical rain forests), other systems are fire-prone and depend on fire in their existence and ecological characteristics (e.g. in savannas). In this paper, I show the different sides of fire, trying to elucidate its evolutionary and ecological role in fire-prone ecosystems and the consequences of wildfires in fire-sensitive ecosystems. Finally, I make a case for the need to debate how the misinterpretation of the role of fire as being always the “bad guy” can threaten fire-prone, but protect fire-sensitive vegetation.
Keywords: Fire management; Fire-prone ecosystems; Fire-sensitive ecosystems; Savannas; Tropical rain forests; Wildfire